Oncogene proteins and proliferation antigens in thymomas: increased expression of epidermal growth factor receptor and Ki67 antigen. Issue 5 (May 1995) - Gilhus, N E; Jones, M; Turley, H; Gatter, K C; Nagvekar, N; Newsom-Davis, J; Willcox, N
Abstract : AIMS--To examine thymomas for proteins encoded by oncogenes and to determine whether their presence correlates with tumour growth and associated myasthenia gravis. METHODS--Sections of 24 thymomas were incubated with anti-EGF receptor (EGF-R), anti-Ki67 antigen, anti-p53, and anti-bcl-2 antibodies, and then stained using the alkaline phosphatase/anti-alkaline phosphatase (APAAP) technique. Cell suspensions and epithelial cell cultures from some of the tumours were also studied. RESULTS--Whereas EGF-R expression was not detected in any of the controls (but only in a 20 week old fetus), it was detected in neoplastic epithelial cells of all thymomas, and was most strongly expressed in metastases and in samples from donors with severe myasthenia gravis. Ki67 labelling was also increased, especially in the larger thymomas. Epithelial expression of both of these markers was confirmed in fresh cell suspensions and monolayer cultures from the five available cases. In contrast, p53 and bcl-2 were not detected in the neoplastic cells, but bcl-2 was present in the intermingling thymocytes. CONCLUSIONS--Neoplastic thymoma cells express EGF-R and Ki67, but there is no concomitant increase in the expression of p53 and bcl-2 proteins. Increased EGF-R expression may result in increased proliferation of neoplastic cells and also in myasthenia gravis. Measurement of EGF-R concentrations may be of prognostic value. The bcl-2 staining pattern in T lymphocytes illustrates the broad spectrum of maturational stages in thymoma lymphocytes.